2020
DOI: 10.3390/ijerph17072453
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Variability and Abundance of Mosquitoes on Dengue Transmission in Central Vietnam

Abstract: Dengue fever is an important arboviral disease in many countries. Its incidence has increased during the last decade in central Vietnam. Most dengue studies in Vietnam focused on the northern area (Hanoi) and southern regions but not on central Vietnam. Dengue transmission dynamics and relevant environmental risk factors in central Vietnam are not understood. This study aimed to evaluate spatiotemporal patterns of dengue fever in central Vietnam and effects of climatic factors and abundance of mosquitoes on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…This result is in accordance with global observations for dengue, chikungunya and Zika ( Wallace et al., 2018 ) where temperature has been shown as an important factor to explain time series of dengue cases across the globe ( Stoddard et al., 2014 ; Chuang et al., 2017 ; Siraj et al., 2017 ; Oidtman et al., 2019 ). However, at the reduced spatial scale of this study we also found an impact for NDVI, a factor that has been reported as significant for dengue transmission dynamics at a country-wide scale in Costa Rica ( Fuller et al., 2009 ) and Vietnam ( Nguyen et al., 2020 ). This result might be related to the fact that vegetation growth is associated with several weather variables, like rainfall and temperature ( Pettorelli et al., 2005 ).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…This result is in accordance with global observations for dengue, chikungunya and Zika ( Wallace et al., 2018 ) where temperature has been shown as an important factor to explain time series of dengue cases across the globe ( Stoddard et al., 2014 ; Chuang et al., 2017 ; Siraj et al., 2017 ; Oidtman et al., 2019 ). However, at the reduced spatial scale of this study we also found an impact for NDVI, a factor that has been reported as significant for dengue transmission dynamics at a country-wide scale in Costa Rica ( Fuller et al., 2009 ) and Vietnam ( Nguyen et al., 2020 ). This result might be related to the fact that vegetation growth is associated with several weather variables, like rainfall and temperature ( Pettorelli et al., 2005 ).…”
Section: Discussionsupporting
confidence: 48%
“…Overall, our results also highlight the value of environmental information derived from satellite images for the surveillance of Ae. aegypti and the arboviruses it transmits, as documented in Southeast Asia ( Nguyen et al., 2020 ). This pattern has also been observed for Culex pipiens L. and West Nile virus transmission in the USA ( Chuang et al., 2012 ; Chuang & Wimberly, 2012 ; Poh et al., 2019 ); and Anopheles albimanus (Wiedemann) abundance and malaria infection in Mesoamerica ( Hurtado et al., 2018a , b ; Rejmankova et al., 1993 ; Rigg et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khanh Hoa is hyper endemic for dengue fever, and was a major hotspot among the 11 provinces in the central Vietnam with an average of 39,876 cases/100,000 population/year during 2011–2018 [ 21 , 44 ]. Dengue incidence peaked at 40,204 cases /100,000 in 2016, and decreased to 920/100,000 in 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Climatic factors such as temperature, humidity, and rainfall [43], [44], [45] [46] can prolong the transmission period of DHF [47]. Temperatures of 24-39°C play a significant role in mosquitoes' development, survival, and feeding behavior to promote viral replication in vectors [48]; thus, DHF will increase by 35% per 1°C [49].…”
Section: The Incidence Rate Of Dhf Based On Climatic Factorsmentioning
confidence: 99%